Photophysics of a UV‐B Filter 4‐Methylbenzylidene Camphor: Intersystem Crossing Plays an Important Role - Fang, Ye‐Guang; Li, Chun‐Xiang; Chang, Xue‐Ping; Cui, Ganglong (Chemphyschem, 2018)
4‐Methylbenzylidene camphor (4MBC) is a frequently used ultraviolet (UV) filter in commercial sunscreens, which is experimentally found to undergo efficient intersystem crossing to triplet manifolds followed by predominant radiationless decay to the ground state. However, its photophysical mechanism is unclear. Herein, we have employed combined CASPT2 and CASSCF methods to study the spectroscopic properties, geometric and electronic structures, conical intersections and crossing points, and excited‐state deactivation channels of 4MBC. We have found that the V(1ππ*) state is populated with large probability in the Franck–Condon region. Starting from this state, there are two efficient nonradiative relaxation processes to populate the 3ππ* state. In the first one, the V(1ππ*) state decays to the V′(1ππ*) state. The resultant V′(1ππ*) state further jumps to the 1nπ* state by internal conversion at the 1ππ*/1nπ* conical intersection. Then, the 1nπ* state hops to the 3ππ* state through an efficient 1nπ*→3ππ* intersystem crossing process. In the second one, the V(1ππ*) state can diabatically relax along the photoisomerization reaction coordinate. In this process, a 1ππ*/3nπ* crossing point helps the 1ππ* system decay to the 3nπ* state, which further decays to the 3ππ* state through internal conversion at the 3nπ*/3ππ* conical intersection. Once the 3ππ* state is formed, a nearly barrierless relaxation path drives the 3ππ* system to hop to the S0 state via the 3ππ*/S0 crossing point. Our current work not only rationalizes recent experimental observations but also enriches our photophysical knowledge of UV filters. Sunscreen states: Electronic structure calculations unveil several efficient nonradiative channels for 4‐methylbenzylidene to decay from an initially populated excited singlet to ground states. The relaxation is overall divided into two phases. First, the lowest triplet state is populated by a series of internal conversion and intersystem crossing processes; then, the ground state is arrived at through another intersystem crossing process.